PENGARUH LUAS POLA PENGGUNAAN LAHAN DAN KONDISI FISIK LINGKUNGAN TERHADAP DEBIT AIR DAN SEDIMENTASI PADA BEBERAPA DAERAH TANGKAPAN AIR (Catchment area) DI SUB DAS CIMANUK HULU JAWA BARAT - Abdul Rahman (Universitas Tadulako, 2009)
The research objective was to study the influence of the area of land use pattern and physical environment condition on land and water resource degradation through river water debit identification including its intensity and fluctuation, and sedimentation. The research object covered 12 water catchment areas which area spread at Upper Cimanuk watershed, West Java. Analysis model applied in this research was a multiple regression for determining a correlation between independent variable (X) and dependent variable (Y) on water catchment area unit as in Draper and Smith (1992). Research results indicated that mixed farming system, rice field area and stream form coefficient increased sedimentation. Increasing settlement area and average rainfall per year augmented annual water debit average. Upland farming increased debit fluctuation, annual debit average and sedimentation. The larger the stream form coefficient and community forest the smaller the annual debit average. Whereas the larger the water catchment area the smaller the stream debit fluctuation.